Pengembangan Gateway untuk Mendukung Proses Over The Air Firmware Update pada Perangkat WSN berbasis Bluetooth Low Energy - Edo Bayu Cahyono; Agung Setia Budi; Sabriansyah Rizqika Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
In research using Internet of Things, there is one component that uses the Wireless Sensor Network. In implementing on WSN, regular firmware update are needed to fix bug, security update and other problems. One of the obstacles when carrying out the firmware update process is if the system is implemented in a remote location such as being outside the city, it will take more time and effort to be able to update the firmware. By using the Over The Air firmware update method, users can update the system without need to go to the device location. However, there are WSN modules that cannot directly connect to the internet. Therefore, a gateway is used to bridge the process of sending firmware update using Bluetooth Low Energy. When an update is needed, the user will update the firmware via a computer or laptop that is connected to the internet. The data will be stored on firebase and will be downloaded by gateway. The gateway used uses the RaspberryPi 3 model B+ microcontroller. After the data is downloaded, it will be sent to the node named ESP32 microcontroller using BLE. Test were carried out to test the long delivery time using BLE based on the size of the data and the distance between the gateway and the ESP32 node. Fore sending 227 kB data sent at a distance of 5 meters it takes an average of 29 minutes 52 seconds and for 954 kB data sent at a distance of 5 meters it takes an average time of 1 hour 57 minutes 30 seconds. Because the BLE delivery is done per Byte so it will be sent one by one.